The Contribution of the Ummat Islam Association (PUI) to the Dynamics of Educational Institutions in Indonesia (1962-2000) - Fuadah, Anis; Ansori, M Afif; Andari, An An; Nasution, Ahmad Taufik; Sudarmin, Sudarmin (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This research examines the changes and continuity of the Islamic Community Association in education from 1969 to 2000. This study employs a qualitative descriptive library research method using a historical approach. The research findings indicate that since 1911, the Ulama Association has pioneered modern educational patterns by integrating religious education, general education, and life skills learning (entrepreneurship). This educational institution encompasses 282 Non-Formal Islamic Schools (Madrasah Diniyah), 308 Kindergartens and Islamic Education Centers (TK, RA, TPA), 165 Elementary Schools (Madrasah Ibtidaiyah), 93 Junior High Schools (Madrasah Tsanawiyah), 47 Senior High Schools (Madrasah Aliyah), 7 Universities, 83 Islamic Boarding Schools (Pondok Pesantren), and 1200 Study Groups (Majlis Ta’lim) spread across Java, particularly in West Java, and partly in South Sumatra.